A Narrative Review of Natural Bioactive Agents for Wound Healing: Mechanistic Insights on Anti-Inflammatory, Angiogenic, Antimicrobial, and Tissue Regeneration Pathways - Nur Afni (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Wound healing is a complex biological process involving the coordinated progression of hemostasis, inflammation, proliferation, and extracellular matrix (ECM) remodeling. Chronic and infected wounds often fail to progress through these stages due to persistent inflammation, oxidative stress, and microbial biofilm formation. In recent years, natural bioactive compounds have gained attention as potential therapeutic agents due to their multi-target biological functions and biocompatibility. This review synthesizes evidence from original in vitro, in vivo, and clinical studies to evaluate the mechanisms of natural compounds, including curcumin, Centella asiatica derivatives, honey-based molecules, flavonoids, and chitosan biomaterials in modulating the wound-healing process. The findings demonstrate that natural compounds can enhance platelet-mediated hemostasis, suppress inflammatory cytokines through NF-κB inhibition and Nrf2 activation, stimulate angiogenesis via VEGF and TGF-β signaling, promote fibroblast proliferation and collagen synthesis, and exert antimicrobial and antibiofilm effects against drug-resistant pathogens. Formulation strategies such as hydrogels and nanoparticle delivery systems were also shown to improve compound stability, tissue penetration, and therapeutic outcomes. These results indicate that natural bioactive wound-healing agents provide a promising avenue for managing both acute and chronic wounds, particularly in contexts where antibiotic resistance or delayed healing presents clinical challenges.